Facilitation of self-empowerment of women living with borderline personality disorder: A concept analysis - N. Ntshingila; A. Temane; M. Poggenpoel; C. P.H. Myburgh (AOSIS, 2016)
Background: Borderline personality disorder is characterised by a pattern of instability in interpersonal relationships, self-image, affects and marked impulsivity. Objective: : The objective is to define the central concept of "facilitation of self empowerment". Method: Analysis and synthesis reasoning methods as indicated by Walker and Avant (2011) were used to define the central concept. Results: A definition of the concept "facilitation of self-empowerment" was formulated from the dictionary and subject definitions. Conclusion: The central concept is important for developing a model as a frame of reference to assist psychiatric nurse practitioners in facilitating the mental health of women living with borderline personality disorder.